PENGARUH NET PROFIT MARGIN, WORKING CAPITAL TURNOVER DAN DEBT TO EQUITY RATIO TERHADAP FINANCIAL DISTRESS PADA SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018-2023 - Submission JORAPI; Sandrina Latief Firdaus; Siti Nur’aidawati (Journal of Research and Publication Innovation, 2024)
This study aims to provide empirical evidence of the effect of Net Profit Margin, Working Capital Turnover, and Debt to Equity Ratio on Financial distress . The type of research used is quantitative descriptive in nature and the data used is secondary data in the form of financial reports. This study uses a sample of food and beverage sub-sector companies listed on the Indonesia Stock Exchange during the 2018-2023 period. Determination of the sample using purposive sampling in order to obtain 12 companies with a total sample of 72 units of analysis. Data analysis in this study uses panel data analysis using Eviews 12 software. The results showed finansial partial effect of Net Profit Margin on Financial distress where the t-count value is 0.310419 < t table 1,99546893 with a significant value of 0.7572 > 0,05,. Working Capital Turnover partially affects on Financial distress where the t-count value is 4.102105 > t table 1,99546893 with a significant value of 0.0001 < 0,05, Debt to Equity Rasio partially affects on Financial distress where the t-count value is -3.206088 > t table 1,99546893 with a significant value of 0.0021 < 0,05. Simultaneously Net Profit Margin, Working Capital Turnover dan Debt to Equity Ratio have an effect on Financial distress where the F-count value is 7.535781 > F table 2,7395 with a significant value of 0,00200 < 0,05. While the coefficient of determination (R²) value is 21,63% the remaining 78,37% is influenced by other variables not examined.